Islamic Economics as a Science and System - Abd. Kholik Khoerulloh; Syifa Rohmaniatul Hidayah (UIN Sunan Gunung Djati, 2021)
Understanding a thing as a whole must begin with understanding the nature of science itself. Islamic economics as a science has received rejection from western scientists because of its value-free nature. However, Islamic economics is not entirely a doctrine and normative assumptions, because the Qur'an and hadith as the main legal basis for Muslims contain many descriptive assumptions that can be verified by modern science. Using a qualitative approach and conducting ontological studies to understand Islamic economics better, it is deemed necessary to see Islamic economics as a system that is full of spiritual values without neglecting the material values contained in this research. being the basis of Islamic economics contains many descriptive arguments that can be proven by modern science.